Capacidades de organizaciones vecinales para la gobernanza urbana: caso de estudio en el municipio de Guadalajara (Estudios) - Tellez Arana, Luis (2020)
The objective of the article is to study the capacities of neighborhood councils in the individual, organizational and institutional dimensions, in order to observe if the capacities of the neighborhood councils constitutes a limitation to their potential of action and then, to the possibility of contribution to urban governance. The study is applied to a sample of neighborhood councils in the city of Guadalajara, Jalisco, Mexico. The main results is that the neighborhood councils have some limitations because they are weakly established and rudimentary institutionalized organizations. Recommendations are made to strength the capacities of neighborhood councils.